Changes in traditional risk factors no longer explain time trends in cardiovascular mortality and its socioeconomic differences. Issue 3 (13th February 2008) - Harald, K; Koskinen, S; Jousilahti, P; Torppa, J; Vartiainen, E; Salomaa, V
Abstract : Aim: To investigate to what extent the changes in traditional risk factors (total cholesterol, smoking, hypertension) explain the changes in socioeconomic (defined by occupational class and household income) differences in cardiovascular mortality in Finland during the past 20 years. Design: Study population comprised 14 642 men and women aged 35–64 years who were selected from population-based FINRISK surveys in 1987, 1992, 1997 or 2002 in three areas of Finland. The 1982 and 1987 FINRISK cohorts were used to determine a model for the probability of cardiovascular death based on risk factor values at the baseline for each socioeconomic group. These predicted changes in cardiovascular mortality were then contrasted with observed mortality rates in different socioeconomic groups to determine the contribution of the changes in risk factors to changes in actual mortality. Results: We found that among men during 1987–97, when risk factor levels were improving in all socioeconomic groups, the model explained 29–44% of the observed mortality decline. The risk factors explained a larger part of the decline among lower socioeconomic groups. During the period 1997–2002 the risk factor levels stopped improving in all socioeconomic groups but observed mortality rates kept declining. The predicted mortality rates were 16–34% of the observed rates during the period 1987–2002. Conclusions: Changes in traditional risk factors no longer provide a good explanation of the changes in cardiovascular mortality and its socioeconomic differences. However, risk factors did explain the cardiovascular mortality decline among lower socioeconomic groups.